Enzyme engineering : selective catalysts for applications in biotechnology, organic chemistry, and life science /: selective catalysts for applications in biotechnology, organic chemistry, and life science. (2023) - Reetz, Manfred T; Sun, Zhoutong; Qu, Ge
No abstract available